Peran Fungi Mikoriza Arbuskula dan Irigasi Tetes dalam Meningkatkan Pertumbuhan Tanaman Pakcoy (Brassica rappa L.) DiLahan Kering - Pareira, Magdalena Sunarty (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
The study aims to determine the interaction and effect of drip irrigation on increasing the growth of pak choi plants in dry land. This study used a completely randomized design with a 3x3 pattern, so that there were 9 treatment combinations repeated 4 times so that there were 36 experimental units. The factors are the first factor, the provision of AMF consisting of three levels, namely M0: without AMF, M1: 10 grams of AMF inoculant per polybag, and M2: 30 grams of AMF inoculant per polybag. The second factor, watering arrangements consisting of three levels, namely P0: watering every morning and evening, P1: watering once every 2 days in the morning and evening, and P2: watering once every 4 days in the morning and evening. So that there are combinations of treatments are M0P0, M0P1, M0P2, M1P0, M1P1, M1P2, M2P0, M2P1 and M2P2. . The results of the study showed that the correct dosage of AMF was 30 grams per polybag in each treatment, while the routine watering time in the morning and evening was the best watering arrangement in increasing the growth and yield of pak choi plants. The combination of 30 grams of AMF with routine watering arrangements in the morning and evening with drip irrigation gave the best results for the parameters of plant height, number of leaves, and fresh weight of plants.